Analysis of Real Option Valuation Method for High-tech Start-Up Enterprises - Meng Zhou (Forest Chemicals Review, 1970)
Under the background that the development of high and new technology has become an important feature of the era of knowledge economy, high and new technology start-up enterprises have continuously increased their proportion in economic growth and become an important driving force to promote the positive development of society. In this paper, combined with the characteristics of high-tech start-up enterprises, new ideas of their value assessment are explored, and scientific and reasonable valuation methods are used to measure their real value, which is helpful to promote the development of such investment and financing. From the perspective of strategic investors, projects depend on each other and interact with each other, which makes projects have strategic value. The concept of real option assessment is introduced into the valuation method, and the equity value of high-tech start-up enterprises is assessed by using the pricing model. In order to achieve high growth or face complex operation conditions, project investment also needs to adjust its decision-making with the change of environment.